Investigation of Heat Treatment Strategies for Additively-Manufactured Tools of X37CrMoV5-1 - Daniel Junker; Oliver Hentschel; Michael Schmidt; Marion Merklein (Metals, 2018)
For cost-intensive products like automobiles, clients often with to personalize their product; this forces the industry to create a large diversity of combinable parts. Additionally, the life cycles of many components become shorter. For highly-stressable parts, which are commonly manufactured by forging, the short changeover cycles result in expensive products, as the costs of tools must be offset by the sale of only a few parts. To reduce the tool cost, new, flexible processes have to be established in tool manufacturing. Laser-based additive manufacturing is noted for its high flexibility; notably, Laser Metal Deposition (LMD) is gaining increasing relevance in research, as it is already used for coating and repairing forming tools; this technology makes it possible to add material onto free-formed surfaces. Therefore, investigations are being conducted to qualify this process to produce forging tools. Due to the thermal processes which are required during additive manufacturing, the microstructure of the material differs from that of wrought material. This, in turn, affects the strategy of post heat treatment in order that the required mechanical properties for tools be attained. Within this manuscript, the influence of additive manufacturing on performance characteristics of hot work tool steel X37CrMoV5-1 (1.2343) is analyzed. To investigate the behavior of additive manufactured material during the process chain of tool manufacturing, properties for different states of a heat treatment are characterized by hardness and strength. It was shown that the strength of the additive manufactured material could be increased compared to wrought material by using a tailored heat treatment. The effects that cause this behavior are investigated by comparing the microstructure at different states of heat treatment.